Overview of Boron Neutron Capture Therapy: a Medical Aspect - Alan Anderson Bangun; Bagaswoto Poedjomartono (Universitas Gadjah Mada, 2018)
Cancer is an abnormal growth of a cell due to the cell’s inability to control and maintain its proliferation, differentiation and apoptosis cycle. There are several methods to treat cancer; one of which is boron neutron capture therapy (BNCT). BNCT is a radiation modality by which a high radiation dose is delivered to tumor cells with lower damage to surrounding normal tissue. This modality has been used widely as a treatment for several cancer cases, such as head and neck cancer, breast cancer, and liver cancer. BNCT uses sodium borocaptate (BSH) or boronophenylalanine (BPA) as the delivery agent. Then, the tumor cell is irradiated by thermal radiation. This technique has excellent potential to become a main method of cancer therapy in the future, since it is noninvasive and has fewer side effects than other methods. Further studies on BNCT are needed to improve its performance as a cancer treatment modality.